2016
DOI: 10.1016/j.bbr.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic activation of locomotor behavior and posture in one-day old rats

Abstract: The purpose of this study was to determine what dose of quipazine, a serotonergic agonist, facilitates air-stepping and induces postural control and patterns of locomotion in newborn rats. Subjects in both experiments were 1-day-old rat pups. In Experiment 1, pups were restrained and tested for air-stepping in a 35-min test session. Immediately following a 5-min baseline, pups were treated with quipazine (1.0, 3.0, or 10.0 mg/kg) or saline (vehicle control), administered intraperitoneally in a 50 microliter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Noradrenaline released by sympathetic nerve fibres and noradrenergic nuclei support the activation and control of spinal motor output. Swann et al [47] demonstrated that the administration of quipazine, a serotonin receptor agonist, improved movement and body posture in independently moving newborn rat. Sławińska et al [48] also showed that the administration of serotonin receptor agonists increases the agility of the hind limbs in rats with paraplegia of the hind limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Noradrenaline released by sympathetic nerve fibres and noradrenergic nuclei support the activation and control of spinal motor output. Swann et al [47] demonstrated that the administration of quipazine, a serotonin receptor agonist, improved movement and body posture in independently moving newborn rat. Sławińska et al [48] also showed that the administration of serotonin receptor agonists increases the agility of the hind limbs in rats with paraplegia of the hind limbs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when newborn rats are suspended in a sling, airstepping may be evoked by treatment with the dopamine precursor L -DOPA [184] or the 5-HT 2A receptor agonist quipazine [185]. Both L -DOPA-induced and quipazine-induced air-stepping produce alternating limb kinematic patterns consistent with walking locomotion [186,187]. A mid-or low-thoracic spinal transection eliminates L -DOPA-induced hindlimb stepping [188], however it does not eliminate quipazine-induced stepping [120,121,188,189], suggesting that 5-HT receptors in the spinal cord engage spinal Fig.…”
Section: Stimulation Of Stepping Behavior In Vivomentioning
confidence: 99%
“…locomotor networks. Pharmacological stimulation of air-stepping has led to better understanding of the development [120,190,191], mechanisms [188,192], function [187], and sensory modulation [121,185] of locomotor circuits in vivo, including for animals with SCI [119,189,193,194].…”
Section: Stimulation Of Stepping Behavior In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of the locomotion, from pregnancy until adolescence, does not involve a single system, but it depends on a variety of systems, such as the sensory, motor, and postural systems and neurotransmitters [ 62 ]. During the long period of neural maturation there are critical periods that are subject to internal and external influences, inducing various behavioral effects [ 63 ].…”
Section: Effects Of Envenomation During Pregnancy On Postnatal Develomentioning
confidence: 99%